Big data and competition analysis under Australian competition law: comeback of the structuralist approach?. (21st December 2020) - Balasingham, Baskaran; Jordan, Hannah
Abstract: Competition assessment in Australia has traditionally been based on an evaluation of the market structure relying on five factors, namely the degree of market concentration, the height of barriers to entry, the extent of product differentiation, the extent of vertical integration, and the nature of arrangements between firms. These factors, known as the 'QCMA factors', are characteristic of competition in the manufacturing industries of the 'old economy'. Since the ascendancy of Chicago and Post-Chicago School thinking competition analysis in Australia has also taken into consideration non-structural factors. However, in light of the dominance of big tech companies in online markets, the so-called 'Neo-Brandeisian School' has advocated focusing on structural elements that are characteristic of online markets. This article examines to what extent the QCMA factors still a suitable structural framework for the assessment of competition in online markets.